Featured Cover. (21st April 2020) - Shi, Zheng‐yuan; Liu, Ya‐ou; Gu, Hong‐yan; Xu, Xi‐qiao; Yan, Can; Yang, Xin‐yu; Yan, Dan
Abstract : The cover image is based on the Original Article* Population Pharmacokinetics of High‐Dose Methotrexate in Chinese Pediatric Patients with Medulloblastoma by Dan Yan** et al., https://doi.org/10.1002/bdd.2221 .***